Exploring History Teachers' Understanding of Using Local History Projects to Develop Learner's Historical Skills - Zwelinjane Mbatha; Boitumelo Moreeng (Studies in Learning and Teaching, 2024)
In this empirical study, we explore the understanding of Social Science teachers on using local history projects to develop learners' historical skills. Teaching local history projects can potentially develop learners' different historical skills as it forces one to compare perspectives, reflect, and re-conceptualise past people and events and locate their places in the present. To achieve the study's aims and objectives, the study employs critical pedagogy as a conceptual framework guiding the study along with an interpretive paradigm that will guide the qualitative approach. The study purposefully sampled five participants from five different schools. Semi-structured interviews and document analysis were used as data collection strategies. The researcher's findings show that no opportunities were created to explore history teachers' understanding of using local history projects to develop learners' historical skills. The paper suggests that the lesson study approach is a valuable intervention that can better the teachers' understanding to establish learners' historical skills. To achieve this, the teachers need workshops on local history projects to develop students' historical skills in schools.